Die Trinitätslehre als tragende Struktur der Fundamentaltheologie: das Beispiel Richards von St.-Victor - Hofmann, Peter (Zeitschrift für katholische Theologie, 2001)
The query of God's Trinity is acknowledged to be something specifical Christian but also seems to be of no importance in Fundamental Theology. There must be a personal quality in God himself, if he really is creator and redeemer (1). Richard of Sanct-Victor developed an idea of God according to this in the 12th century (De Trinitate). He speaks of God relating to real experience and possibility of human love (charitas), but he does not argue with christian manifestation. God himself is a personal Trinity in analogy to personal communication of men. He wants to prove this with "rationes necessariae" (2). But he does not use something like "natural reason" perceiving God by itself. The light of divine reason lightens the creation and enables human perception or reason. A "First Philosophy" in Theology may use this argument answering for christan believe (3).